Normothermic Machine Perfusion of Deceased Donor Liver Grafts Is Associated With Improved Postreperfusion Hemodynamics. Issue 9 (September 2016) - Angelico, Roberta; Perera, M. Thamara P. R; Ravikumar, Reena; Holroyd, David; Coussios, Constantin; Mergental, Hynek; Isaac, John R.; Iqbal, Asim; Cilliers, Hentie; Muiesan, Paolo; Friend, Peter J.; Mirza, Darius F.
Abstract : Background: Graft reperfusion poses a critical challenge during liver transplantation and can be associated with hemodynamic instability/postreperfusion syndrome. This is sequel to ischemia-reperfusion injury and normothermic machine preservation (NMP) may affect hemodynamic changes. Herein, we characterize postreperfusion hemodynamics in liver grafts after NMP and traditional cold preservation. Materials and methods: Intraoperative records of patients receiving grafts after NMP (n = 6; NMP group) and cold storage (CS) (n = 12; CS group) were compared. The mean arterial pressure (MAP) was defined as the average pressure in the radial artery during 1 cardiac cycle by invasive monitoring. Postreperfusion syndrome was defined as MAP drop greater than 30% of baseline, lasting for 1 minute or longer within the first 5 minutes from graft reperfusion. Results: Donor, recipient, demographics, and surgical parameters were evenly matched. Normothermic machine preservation grafts were perfused for 525 minutes (395-605 minutes) after initial cold ischemic time of 91 minutes (73-117 minutes), whereas in CS group cold ischemic time was 456 minutes (347-685 minutes) ( P = 0.001). None developed postreperfusion syndrome in the NMP group against n = 2 (16.7%) in CS group ( P = 0.529). Normothermic machine preservation group had better intraoperative MAP at 90 minutes postreperfusion ( P = 0.029), achieved with a significantly less vasopressor requirement ( P = <0.05) and less transfusion of blood products ( P = 0.030) compared with CS group. Conclusions: Normothermic machine perfusion is associated with a stable intraoperative hemodynamic profile postreperfusion, requiring significantly less vasopressor infusions and blood product transfusion after graft reperfusion and may have benefit to alleviate ischemia-reperfusion injury in liver transplantation.